(untitled) (Journal of Pharma Insights and Research, 2023)
This case report discusses about a 49-year-old male with grade I hepatic encephalopathy, a complication of chronic alcoholic liver disease. With a 20-year history of heavy alcohol consumption and recent cirrhosis diagnosis, the patient presented symptoms such as confusion, disorientation, drowsiness, and abdominal distension. Physical examination revealed icterus, pitting edema, hepatomegaly, and mild ascites. The comprehensive treatment regimen addressed various aspects of the patient’s condition. Lactulose syrup reduced gut ammonia levels, ceftriaxone and rifaximin prevented enteric infections, and a frusemide/spironolactone combination reduced ascitic fluid. Vitamin B supplements aided neurological repair, dexamethasone served for its anti-inflammatory effects, and protein supplements corrected malnutrition. Liver supportive measures included alcohol abstinence and paracentesis to drain excess ascitic fluid. The patient exhibited significant improvement in symptoms and laboratory parameters during the hospital stay. Liver and kidney function tests normalized, and coagulation profiles steadily improved. Confusion and disorientation resolved completely, and repeat ultrasound confirmed a reduction in ascitic fluid. The patient was discharged in a stable condition. This case highlights the importance of a holistic therapeutic approach to effectively manage grade I hepatic encephalopathy secondary to alcoholic liver cirrhosis. Addressing multiple contributing factors, including abstaining from alcohol and employing pharmacological, nutritional, and procedural interventions, can lead to the reversal of mild hepatic encephalopathy